Reevaluating the Effectiveness of Peacekeeping and SDG 16 in Africa: Challenges in Combating Ethnic Conflict - Abhigita, Emanuela Nandin (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
After almost 10 years into the Sustainable Development Goals (SDGs), the African continent remains left behind in many points of the SDG, including SDG 16 “Peace, Justice, and Strong Institution”. Many of the world’s current issues of armed conflict and territorial disputes still reside in the continent. While many new factors of armed conflict surfaced throughout the decade, a dominant issue remains a big hurdle in bringing peace to Africa, ethnic conflict. In order to solve ethnic conflicts, international efforts of peacekeeping become one of the most used strategies in the hopes to combat these issues. As of 2023, 6 out of the 12 ongoing global United Nations peacekeeping operations still reside in Africa. However, the issue of ethnic conflict remains prevalent and peacekeeping seems to be ineffective in de-escalating it. Using peacekeeping as third-party mediation theory by A.B. Fetherston, this article identifies that whilst UN Peacekeeping is relatively successful in conflict control, it still struggles with resolution processes which prevents long-term peace and resolution to take place. This article also identifies the lack of UN Peacekeeping capability in addressing local conflicts and the complexities of ethnic based-conflict, as well biases in peacekeeping operations contribute to effectiveness. This article also urges the need for greater communication between UN Peacekeeping and local actors, and regional bodies, as well as a more comprehensive training for peacekeeping in handling ethnic conflict. Key Words: ethnic conflict, SDG 16, peacekeeping, Africa